قياس سماكة اللطخة الصفراء بواسطة )ال OCT ( تصوير التماسك البصري المقطعي لمرضى السكري - سليمان يوسف; كردغلي نجوى; سيد رضا برسي سيد مصطفى (Latakia University Journal -Medical Sciences Series, 2018)
الOCT وسيلة تشخيصية حديته لفحص الأنسجة بشكل غير جارح .بدئ استخدامها في الممارسة السريرية منذ عام 1995 ويشبه تصوير التماسك البصري المقطعي التصوير بالأمواج فوق الصوتية من حيث أنه يعتمد مبدأ التقاط الصدى إلا الأمواج الضوئية بدلاً من الأمواج فوق الصوتية إن إمكان ية الحصول على صور للشبكية عالية التباين وإعادتها بسهولة بشكل غير جارح جعلت هذا الفحص مهما جداً في الأمراض الشبكية المترافقة بإصابة اللطخة الصفراء. لذلك هدفنا هو دراسة احصائية لقيم لثخانة اللطخة الصفراء بواسطة تصوير التماسك البصري المقطعي وعلاقة كل منها بالعمر والجنس والعلاج والقدرة البصرية وفترة المرض لدى مرضى السكري, لذلك يعد القياس الدقيق لسماكة اللطخة الصفراء هاماً من اجل متابعة تقدم المرض وتقييم العلاج والتشخيص الدقيق لآفات حدة الأبصار. ثخانة اللطخة في العينين كان ت أكبر عند الذكور من الإناث , نلاحظ بأن القدرة البصرية تتناقص مع العمر, وبالنسبة لكلتا العينين نلاحظ بأن ثخانة اللطخة تزداد مع العمر وارتباط ايجابية بين ثخانة اللطخة في كلتا العينين وبين مدة المرض, ويتبين عدم وجود فروق ذات دلالة احصائية بين الثخانات مع اختلاف نوع العلاج (أنسولين أو حبوب) فنلاحظ وجود علاقة ارتباطية بين القدرة البصرية وثخانة اللطخة في كلتا العينين, حيث تنخفض القدرة البصرية لدى مرضى السكري مع زيادة الثخانة, وفي دراسة الأجزاء المختلفة للطخة فإن الجزء الداخلي أكثر ثخانة من الجزء الخارجي, والجزء الأنفي أكثر ثخانة من أجزاء اللطخة المختلفة, والجزء الداخلي الأنفي أكثر ثخانة. The OCT is a recent diagnostic tool for non-invasive tissue examination, which has been used in clinical practice since 1995. The OCT is similar to the ultrasonic tomography in that it relies on optical waves rather than ultrasound ones. The ability to obtain high-contrast images of the retina in a non-invasive manner has made this examination very important in retinal diseases associated with macula.. Therefore, our objective is to study the statistical values of the measurements of the macular thickness using Optical Coherence Tomography (OCT) and the relationship of each value to age, sex, medication ,duration of diabetes ,and the visual acuity in diabetic eyes. Therefore, the accurate measurement of the macular thickness is important to follow up disease progression, evaluate treatment and accurately diagnose lesions of visual acuity. The thickness of the macula in the left and right eye was thicker in males than in females. We find out that the visual ability declines with age. For both left and right eyes, the thickness of the macula increases with age and the content of the macula correlates with its thickness and the period of the disease. There are no statistically significant differences of the thicknesses with different treatment types (insulin or pills),so we notice a correlation between the visual acuity and the thickness of the macula in both eyes ,so that the higher the thickness of the macula in diabetic patients ,the lower the visual acuity . In the study of the different parts of the macula, the internal part is thicker than the external part and the nasal part is thicker than the different parts of the macula, and the naso- internal part is the thickest.